STRATEGI PEDAGANG TUAK DI JALAN ARENGKA DUA KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Simbolon, Lintong; ", Risdayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Thesis titled "Strategies Merchant Tuak street Arengka Dua District of Payung Sekaki" began with the interest the authors look at the phenomenon of the existence of palm wine seller. Wine merchant is one of the informal sector where the activities carried out every hari.Tuak is one of the drinks are included in the group alcoholic, fermented beverage ingredients / fruits that contain sugar. Tuak so that the sellers are required to have a strategy for the business being operated can survive. The strategies used can be either a physical strategy, or appears to be doing other work and add other merchandise and also a strategy that does not look like interaction and social capital committed by wine merchants. This research was conducted in subjects with interviewing owners of existing wine lapo Arengka Dua streets. Results from this study is the result of data analysis of the data obtained through interviews and observations conducted.Keywords: Profile, Strategy, Informal Sector.